2001
DOI: 10.1046/j.1365-294x.2001.01303.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic structure and distinctness of Apis mellifera L. populations from the Canary Islands

Abstract: The genetic structure of Apis mellifera populations from the Canary Islands has been assessed by mitochondrial (restriction fragment length polymorphisms of the intergenic transfer RNAleu-COII region) and nuclear (microsatellites) studies. These populations show a low level of genetic variation in terms of average number of alleles and degree of heterozygosity. Significant differences in the distribution of alleles were found in both data sets, confirming the genetic differentiation among some of the islands b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
72
1
6

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 89 publications
(93 citation statements)
references
References 48 publications
(83 reference statements)
14
72
1
6
Order By: Relevance
“…Unlike many populations of A. m. mellifera from western Europe and A. m. iberiensis from the archipelagos of Baleares and Macaronesia , which are threatened by human‐mediated gene flow (De la Rúa et al., 2001, 2003; Jensen et al., 2005; Miguel et al., 2015; Muñoz et al., 2014; Pinto et al., 2014), there is very limited introgression in A. m. iberiensis populations of Iberia (Chávez‐Galarza et al., 2015). Therefore, it is crucial to monitor Iberian populations, before gene complexes shaped by natural selection over evolutionary time are irretrievably lost.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike many populations of A. m. mellifera from western Europe and A. m. iberiensis from the archipelagos of Baleares and Macaronesia , which are threatened by human‐mediated gene flow (De la Rúa et al., 2001, 2003; Jensen et al., 2005; Miguel et al., 2015; Muñoz et al., 2014; Pinto et al., 2014), there is very limited introgression in A. m. iberiensis populations of Iberia (Chávez‐Galarza et al., 2015). Therefore, it is crucial to monitor Iberian populations, before gene complexes shaped by natural selection over evolutionary time are irretrievably lost.…”
Section: Discussionmentioning
confidence: 99%
“…This important Iberian reservoir of genetic diversity has not yet been seriously threatened by C‐lineage introgression (Chávez‐Galarza et al., 2015, 2017; Miguel, Iriondo, Garnery, Sheppard, & Estonba, 2007), although this scenario might change as many young beekeepers are attracted by the advertised benefits of commercial strains—being more prolific and docile. In many islands of the Baleares and Macaronesia, for example where the Iberian honeybee was presumably introduced in historical times, the contemporaneous large‐scale importation of commercial C‐lineage queens has resulted in high levels of introgression into the local populations (De la Rúa, Galián, Serrano, & Moritz, 2001, 2003; Miguel et al., 2015; Muñoz, Pinto, & De la Rúa, 2014). The conservation of A. m. iberiensis diversity is therefore a priority, especially in the light of climate change as this subspecies is well adapted to a broad range of environments, including hot and dry summer months with limited nectar flows.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier microsatellite studies found that the genetic diversity of Macaronesian honey bees is characterized by low values, as reflected by the number of alleles (nA) and heterozigosity (He) values (De la Rúa et al, 2001Rúa et al, , 2006. Despite significant temporal mitochondrial changes detected in the Macaronesian honey bee populations (Muñoz et al, 2013), our present study suggests that nuclear genetic diversity has not varied significantly and has remained relatively low.…”
Section: Discussionmentioning
confidence: 99%
“…As a result of isolation and adaptation to particular environmental island conditions, many organisms have given rise to locally adapted populations, such is the case of the honey bee, Apis mellifera Linneaus 1758. Indeed, honey bee populations locally adapted to endemic Macaronesian flora and particular weather and orography conditions are characterized by particular mitochondrial haplotypes (A11, A14, A15, and A16) belonging to the African evolutionary sub-lineage with Atlantic distribution (De la Rúa et al, 1998, 2001, 2006.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation